The model of description of extraction of uranium-235 and uranium-238 isotopes complexes in a supercritical carbon dioxide layer heated from below - Borts, B.V.; Skoromnaya, S.F.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2022)
The models and analytical solutions for description of the extraction of ²³⁵U and ²³⁸U isotopes complexes in case of availability of water microdrops located both in a uniform temperature field and in a non-uniform temperature field of the heated from bellow horizontal layer of the supercritical carbon dioxide are suggested. It has been indicated that in a uniform temperature field the efficiency of supercritical fluid extraction with carbon dioxide complexes of uranium isotopes reaches a maximum at the limit of water solubility in supercritical carbon dioxide. Theoretical calculations have demonstrated that the maximum concentration of ²³⁵U isotope complexes heated from below in a supercritical carbon dioxide layer reaches 1.2% and is observed near the lower layer boundary. The procedure for supercritical fluid extraction with carbon dioxide is described, in which the concentration of ²³⁵U isotope complexes in the supercritical fluid will be higher than the natural one. Запропоновано моделі та знайдено аналітичні розв'язки для опису екстракції комплексів ізотопів ²³⁵U і ²³⁸U при наявності мікрокрапель води, що знаходяться як в однорідному температурному полі, так і в неоднорідному температурному полі температур шару надкритичного діоксиду вуглецю, що підігрівається знизу. Показано, що в однорідному полі температур ефективність надкритичної флюїдної екстракції діоксидом вуглецю комплексів ізотопів урану досягає максимуму на межі розчинності води в надкритичному діоксиді вуглецю. Теоретичними розрахунками показано, що максимальна концентрація комплексів ізотопів ²³⁵U досягає величини 1,2% у шарі надкритичного діоксиду вуглецю, що підігрівається знизу, і спостерігається поблизу нижньої межі шару. Описано порядок проведення надкритичної флюїдної екстракції діоксидом вуглецю, при якому концентрація комплексів ізотопу ²³⁵U у надкритичному флюїді буде вище природної. Предложены модели и найдены аналитические решения для описания экстракции комплексов изотопов ²³⁵U и ²³⁸U при наличии микрокапель воды, находящихся как в однородном температурном поле, так и в неоднородном поле температуры подогреваемого снизу слоя сверхкритического диоксида углерода. Показано, что в неоднородном поле температур эффективность сверхкритической флюидной экстракции диоксидом углерода комплексов изотопов урана достигает максимума на пределе растворимости воды в сверхкритическом диоксиде углерода. Теоретическими расчетами показано, что в подогреваемом снизу слое сверхкритического диоксида углерода максимальная концентрация комплексов изотопов ²³⁵U достигает величины 1,2% и наблюдается вблизи нижней границы слоя. Описан порядок проведения сверхкритической флюидной экстракции диоксидом углерода, при котором концентрация комплексов изотопа ²³⁵U в сверхкритическом флюиде будет выше природной.